Textbook of diagnostic microbiology (Elsevier/Saunders, 2015)
Offering an introduction to the essentials of diagnostic microbiology, this title helps you develop the problem-solving skills necessary for success in the clinical setting. It follows a 'building block' approach to microbiology that moves progressively from basic concepts to advanced understanding.